Development of urban infrastructure through land-based financing: A case of Bharatpur metropolitan city (Residential area) - Thapa Magar, Aakash; Uprety, Sanajaya (Journal of Innovations in Engineering Education, 2022)
Municipalities in Nepal has been seen as a driving force for development, especially after the federal restructuring of the country. Constitution of Nepal, 2015 and the Local Government Operation Act, 2017 have authorized the local government to increase their revenue base from a wide range of sources including the urban land resources to make them ﬁnancially resourceful for the urban development ﬁnancing. In this context, land-based ﬁnancing is seen as a potential source for ﬁnancing urban infrastructure development in residential areas which lack adequate and decent physical infrastructure. The advantages of infrastructure projects are capitalized on land values which contributes to the land-based ﬁnance instruments to pay for infrastructural development. The purpose of this research was to explore how Bharatpur Metropolitan City might fund the construction of urban infrastructure through land-based ﬁnancing in the residential area lacking adequate and decent infrastructure. Both qualitative and quantitative approaches were used to collect and analysis of existing municipal land-based revenue, land valuation, property registration fees of the case study area, Krishnapur Land Pooling project area, of Ward no 7 of Bharatpur metropolitan city. Building upon the analysis of the capital gain from land value increment and residents’ willingness to pay land-based taxes and users fees in the case study area, the study ﬁnds land-based-tax system was limitedly integrated into the land-use zoning and the land value increment. This has resulted in the disparities of tax rates and tax coverages. This study recommends further study to to replace the Housing and Land Tax with Integrated Property Tax system and reform policies related to “property valuation” based on added calculations according to land-use zoning, land use and resident’s willingness to pay as a means to reinforce municipal revenue to increase infrastructure ﬁnancing in residential areas.